Lansia Rindu Bahagia: Kajian Keluarga Jawa Kelompok Lansia SUCI Banyumanik Semarang - Ayudya Amelia; Afidatul Lathifah; Mudjahirin Thohir (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
Happiness is the right of all human beings, children, adults and parents, they have the right to be happy with different sizes of happiness. This difference in the size of happiness is because each individual has different experiences and life patterns so that the assessment of the expected happiness is also different. The research "Elderly Miss Happy (Case Study: Javanese Family in the SUCI Elderly Group RW 06 and RW 07 Banyumanik District Semarang)" uses symbolic interaction theory. The problem of this research is what and how to measure the happiness of the Javanese ethnic elderly and in what way they endeavor it and what is gained from this happiness, starting from seeing experiences and life patterns, hopes for happiness to the reality of realized happiness. This research uses a phenomenological method. Phenomenology is a method to finding the meaning behind the phenomenon being revealed. Besides that, it also uses qualitative data, primary data sources and secondary data. Primary data sources are from observations and interviews while secondary data sources are from previous research and books.The results of this study are: (1) the measure of elderly happiness is measured by the elderly's meaning of their life experiences. Being a part of the SUCI’s group is positioned as a substitute with children and being happy with other elderly people, (2) when they are aware of their old age, life choices are more oriented towards the happiness of the end of their life and after their death. The method taken is to deepen religious knowledge. They find happiness in the SUCI group because in this group they can more intensively carry out religious activities. This means that the needs of elderly are gathering each others because of the warm interactions between the elderly. The argument given is the awareness that their children have high mobility, causing the family to be busier and less concerned about the elderly so that the elderly who live with the family feel less family support. The relentless nature of Javanese elderly prefers to reduce conflict causes they not to ask their family first, for attention and try to find happiness outside the home. Happiness is present when the elderly join the SUCI elderly group.